Five decades of education at reid avenue: some personal reflections - Samaranayake, V.K. (My University, 2008)
The author began his contact with Reid Avenue in January 1950 when he entered Royal College as a grade 6 student. In 1956 he left school to join the University of Ceylon next door and on graduation in 1961, continued to be with the University as a member of the academic staff thus covering a period of over 54 years at educational institutions around Reid Avenue. During this period many changes have taken place in education and related spheres and these are analysed in the paper from an educational, social and political point of view. The impact these changes have had on national development will also be discussed. Finally how the last 54 years have contributed towards preparing Sri Lanka to face the challenges of the 21st Century will be examined.